The Relationship Between Remnant Cholesterol and Visceral Adipose Tissue: A National Cross-Sectional Study - Wang, Zhaoxiang; Zhong, Shao; Wu, Menghuan; Shao, Xuejing; Gu, Tian; Xu, Mengjiao; Yang, Qichao (Hormone and Metabolic Research, 2024)
The aim of our study is to explore the relationship between remnant cholesterol (RC) levels and visceral adipose tissue (VAT) in the US adult population. This cross-sectional study utilized data from 5301 participants aged 20 to 59 years gathered by the National Health and Nutrition Examination Survey (NHANES). RC was determined by deducting both high-density lipoprotein cholesterol (HDL-c) and low-density lipoprotein cholesterol (LDL-c) from total cholesterol (TC), and VAT was measured using dual-energy X-ray absorptiometry. Visceral obesity is defined as a VAT area ≥ 100 cm2. With increasing quartiles of RC levels, the prevalence of visceral obesity rises (16.51% vs. 36.11% vs. 55.66% vs. 74.48%, p<0.001). After adjusting for confounders, RC levels positively correlate with visceral obesity risk (OR=1.039, 95% CI 1.031–1.048, p<0.001). Additionally, individuals with low LDL-c/high RC and those with high LDL-c/low RC showed 2.908-fold (95% CI 1.995–4.241) and 1.310-fold (95% CI 1.022–1.680) higher risk of visceral obesity, respectively, compared to those with low LDL-c/low RC. Receiver Operating Characteristic (ROC) and Decision Curve Analysis (DCA) show RC’s superior predictive ability over other lipid markers. Subgroup analysis showed that the relationship between RC and visceral obesity was more ronounced in those with cardiovascular disease. Smooth curve fitting indicated a nonlinear relationship between RC levels and VAT area. Our study highlights that elevated levels of RC are associated with adverse accumulation of VAT. However, the causal relationship between RC and visceral obesity requires additional investigation.
Keywords: remnant cholesterol; visceral adipose tissue; visceral obesity; NHANES; population-based study; nonlinear relationship